Directing technical change from fossil-fuel to renewable energy innovation: An empirical application using firm-level patent data - Joëlle Noailly; Roger Smeets (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper investigates the determinants of directed technical change in the electricity generation sector. We use firm-level data on patents led in renewable (REN) and fossil fuel (FF) technologies by about 7,000 European firms over the period 1978-2006. We separately study specialized firms that innovate in only one type of technology during the sample period, and mixed firms that innovate in both technologies. We find that for specialized firms the main drivers of innovation are fossil-fuel prices, market size, and firms' past knowledge stocks. Also, prices and market size drive the entry of new REN firms into innovation. By contrast, we find that innovation by mixed firms is mainly driven by strong path-dependencies since for these firms past knowledge stock is the major driver of the direction of innovation. These results imply that generic environmental policies that affect prices and energy demand are mainly effective in directing innovation by small specialized firms. In order to direct innovation e orts of large mixed corporations with a long history of FF innovation, targeted R&D policies are likely to be more effective.
Keywords: Q4; 330; Directed Technical Change; Energy; Patents; Firms' Dynamics